2015
DOI: 10.1002/hbm.22958
|View full text |Cite
|
Sign up to set email alerts
|

Regional volumes in brain stem and cerebellum are associated with postural impairments in young brain‐injured patients

Abstract: Many patients with traumatic brain injury (TBI) suffer from postural control impairments that can profoundly affect daily life. The cerebellum and brain stem are crucial for the neural control of posture and have been shown to be vulnerable to primary and secondary structural consequences of TBI. The aim of this study was to investigate whether morphometric differences in the brain stem and cerebellum can account for impairments in static and dynamic postural control in TBI. TBI patients (n = 18) and healthy c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 87 publications
5
23
0
Order By: Relevance
“…When scrutinizing the brain areas to which modules 1 and 14 connect both structurally and functionally (figure 5), we found strong mutual connectivity between the anterior and posterior parts of the cerebellum (table 2), which is in agreement with previous work [40,43]. Moreover, the anterior part projects also to the motor cortex among other areas as is also well established [41,44,45].…”
Section: Discussionsupporting
confidence: 90%
“…When scrutinizing the brain areas to which modules 1 and 14 connect both structurally and functionally (figure 5), we found strong mutual connectivity between the anterior and posterior parts of the cerebellum (table 2), which is in agreement with previous work [40,43]. Moreover, the anterior part projects also to the motor cortex among other areas as is also well established [41,44,45].…”
Section: Discussionsupporting
confidence: 90%
“…More precisely, we found a strong decrease in connectivity degree in motor areas, brainstem, cingulate gyrus, cerebellum, and the temporal poles, areas that are typically associated with the performance of motor skills and balance control. Indeed, decreased subcortical connectivity, in particular in the brainstem and cerebellum, was recently associated with postural impairments in TBI patients ( Drijkoningen, Leunissen, et al, 2015 ), suggesting a possible diffuse pathology across subcortical structures.…”
Section: Discussionmentioning
confidence: 99%
“…On a neural level, TBI generally disrupts functional and structural large-scale brain networks (i.e., the networks of white matter tracts connecting different brain regions), while on a behavioral level, TBI often triggers various deficits, including cognitive impairments, motor problems, emotional sequelae, and so forth, that can persist for years postinjury ( Caeyenberghs, Leemans, De Decker, et al, 2012 ; Ham & Sharp, 2012 ; D. H. Smith & Meaney, 2000 ). We focus here on deficits in balance control after TBI, which can last from months to several years after the traumatic impact in both adults ( Guskiewicz, Riemann, Perrin, & Nashner, 1997 ; McCulloch, Buxton, Hackney, & Lowers, 2010 ) and children ( Drijkoningen, Caeyenberghs, Vander Linden, et al, 2015 ; Drijkoningen, Leunissen, et al, 2015 ; Katz-Leurer, Rotem, Lewitus, Keren, & Meyer, 2008 ), which is psychosocially important because it increases the risk of falling, and thus affects the patient’s independence ( McCulloch, Buxton, Hackney, & Lowers, 2010 ; Wade, Canning, Fowler, Felmingham, & Baguley, 1997 ).…”
Section: Introductionmentioning
confidence: 99%
“…Burciu et al (2013) observed that in 20 patients with cerebellar degeneration, two weeks of sensorimotor training lead to both an improvement in postural performances and an increase of gray matter volume in the cerebellum; in a group of patients with Parkinson's disease, Sehm et al (2014) reported a change of grey matter in the right cerebellum, together with an improvement in postural stability after postural training on movable support. Recently, Drijkoningen et al (2015) examined the effect of eight weeks of balance training program in a group of 29 children with traumatic brain injury and they found that the changes in balance control were associated with alterations in the cerebellar white matter microstructure. Finally, our group (Goulème et al, 2015a,b) reported in a small group of dyslexic children an improvement in postural stability after 3 min of postural training in deprived sensory conditions only (eyes closed on an unstable platform), suggesting an improvement in sensory input processing, most likely due to a better cerebellar integration.…”
Section: Discussionmentioning
confidence: 99%